A combined data encryption method with identification of their sender - Волошко, А. В.; Лутчин , Т. М. (Інститут проблем реєстрації інформації НАН України, 2021)
Information security is a particularly important factor as new information technologies are widely introduced, various kinds of branched information and computer systems. Encryption is an effective method of protecting information from unauthorized access when it is transmitted over open communication and storage channels. Analysis of known encryption algorithms showed that symmetric as well as asymmetric algorithms alone do not meet modern requirements. That is, it is necessary at the level of compensation for the shortcomings of symmetric systems, using the advantages of asymmetric, to apply mathematical methods of transformation and the encryption algorithm to increase cryptographic stability. It is offered a generalized method of data encryption with the ability to identify the sender of the message Based on the analysis of generalized models of information flows based on the time-space properties of wavelet coefficients by levels of wavelet decomposition. The encryption private key is a password consisting of four components. Its length is 324 bits. The decryption requires an estimated 1012 operations and a required knowledge of the selected wavelet base. Modified data (wavelet coefficients of information with an encrypted key) is reversed by a wavelet transform, the coefficients of which will be transmitted over the line as a public key. The unauthorized effect on the transmitted data is completely eliminated due to the time-space and spectral properties of the wavelet coefficients by the levels of the wavelet decomposition. The relative error of the inverted wavelet transform is in the range from 4·10–14 to 6·10–14. Tabl.: 3. Fig.: 2. Refs: 15 titles.